(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2024)
Many factors are attributable to the academic achievements of students among which Teachers’ variable is a major attribute. The limitations of the teacher as a supporting agent in the area of Basic Science hinder academic achievement of students in learning of Basic Sciences. The quality of instructions from the teacher at all levels of education determines the acquisition of competencies necessary for self-reliance and effective service delivery. The teacher’s attitude to work, knowledge of subject matter and instructional competence have a relationship with students’ academic achievements. The poor quality of students’ academic quality among community health students’ in Basic Sciences in CrossRiver State may be as a result of these variables. This study therefore examined Teachers’ variable and academic achievement of community health students’ in Basic Sciences in Cross River State. To achieve the purpose of this study, four (4)specific objectives were raised to guide the study, which were then converted to four (4) research questions and transformed to research hypotheses. Related literatures we reviewed in line with the variables of the study. The study adopted correlationalresearch design, which is a non-experimental approach between a set of variables and naturally cannot be manipulated. The research area is Cross River State, Nigeria. The target population of study was year 1 Community Health students. Sample of study was415 students randomly selected from ten schools for the 2023/2024 academic session. The instrument employed was questionnaire designed by the researcher. Cronbach Alpha reliability method was used to determine the reliability estimate of the instrument which range from 0.73 to 0.81. Data was analysed using Multiple Linear regression.The findings of the study revealed that all teachers’variables had significant positive relationship with students’ academic performance in Basic Sciences in Cross River State. It was recommended among others that teachers should adopt positive attitudetowards their teaching profession especially in secondary schools.